Design and Development of Mini Model for Mini Tempeh Packaging System: Wrapper Feeder and Soybean Feeder - Zakaria, Muhammad Ainul Azam; Mohd Harun, Dalila (Progress in Engineering Application and Technology, 2021)
Tempeh is a soybean based food that originated from Indonesia. Tempehs are usually packed manually in small industry, which take a long time to pack it. This research objectives is to determine the concept for wrapper feeder and soybean feeder mechanism system, to design and fabricate the prototype of wrapper feeder and soybean feeder. This study is to produce automated packaging machine tempeh for tempeh industry as a traditional food product and focusing on small scales industry so that they can apply this project for their production. The design of the prototype is made by using SolidWorks software. Prototype will be fabricated based on the design and will operate by using Arduino and electric motor.